IT outsourcing relationship management and performance measurement system effectiveness - Perrin, Brian; Pervan, Graham (Australasian Chapter of the Association for Information Systems, 2005)
Managing the relationship between the client and the vendor is of critical importance to the success of the IT outsourcing arrangement. This paper develops and explores a conceptual model based on relational exchange theory that identifies a number of attributes or dimensions that contribute to the overall success of (a) the relationship, (b) performance measurement system effectiveness and (c) the outsourcing contract. This research supports the proposition that successful management of the relationship positively influences the success of public sector IT outsourcing contracts and the effectiveness of the performance measurement system used. An effective relationship complements the performance measurement system effectiveness.